Analisis Pendapatan, Produktivitas Dan Curahan Tenaga Kerja Usahatani Padi Sawah Pada Petani Pengguna Dan Bukan Pengguna Brigade Alsintan (Alat Dan Mesin Pertanian) Di Kecamatan Pabuaran, Kabupaten Subang - Andi Arifin; Euis Dasipah; Nendah Siti Permana (Paspalum: Jurnal Ilmiah Pertanian, 2022)
This study aims to analyze the effect of using Alsintan (Agricultural Machine Tools) on income, productivity and outpouring of labor  for lowland rice farming. This research uses survey method. The technique for determining respondents used the Taro Yamane formula (1967) and obtained a sample size of 41 respondents who were allocated proportionally, namely 23 farmer respondents who used agricultural machinery and 18 farmer respondents who did not use agricultural machinery. The results showed that the income of lowland rice farmers using agricultural machinery was different from the income of rice farmers who were not using agricultural machinery. The income of lowland rice farmers using agricultural machinery is Rp. 15,117,478, which is Rp. 7,855,255, - compared to the income of rice farmers who do not use machinery, which is only Rp. 7,262,223. The productivity of lowland rice farmers using agricultural machinery is different from that of farmers who are not using agricultural machinery, namely the productivity of lowland rice farmers using agricultural machinery is 6,825 kg/hectare/season, 771.0 kg higher than the productivity of paddy rice for farmers who do not use machinery, which is only 6,066 kg/hectare/season. The outpouring of labor for rice farmers using machine tools is different from the labor for rice farmers not using machine tools, where the labor for rice farmers using machine tools is 69 working days/hectare/season, 42 working days less than rice farmers not using machine tools which is 111 Working Days/hectare/season.